2016
DOI: 10.1371/journal.pone.0153466
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Short Version of MSQOL-54 Using Factor Analysis and Item Response Theory

Abstract: BackgroundThe Multiple Sclerosis Quality of Life-54 (MSQOL-54, 52 items grouped in 12 subscales plus two single items) is the most used MS specific health related quality of life inventory.ObjectiveTo develop a shortened version of the MSQOL-54.MethodsMSQOL-54 dimensionality and metric properties were investigated by confirmatory factor analysis (CFA) and Rasch modelling (Partial Credit Model, PCM) on MSQOL-54s completed by 473 MS patients. Their mean age was 41 years, 65% were women, and median Expanded Disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 39 publications
(54 reference statements)
1
38
0
Order By: Relevance
“…[14][15][16] As observed by Rosato et al in the Italian speaking population, we noted a strong correlation between scores of MSQoL-54 and MSQoL-29. 8 Our data showed that reliability of MSQoL-29 is as good as that of MSQoL-54 7,15 .The MSQoL-29 is as valid and reliable a tool to evaluate QoL in PwMS as MSQoL-54. , When two different methods are measuring the same outcome, it is expected that there would be a moderate correlation based on the simple fact that the outcome being measured is the same.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…[14][15][16] As observed by Rosato et al in the Italian speaking population, we noted a strong correlation between scores of MSQoL-54 and MSQoL-29. 8 Our data showed that reliability of MSQoL-29 is as good as that of MSQoL-54 7,15 .The MSQoL-29 is as valid and reliable a tool to evaluate QoL in PwMS as MSQoL-54. , When two different methods are measuring the same outcome, it is expected that there would be a moderate correlation based on the simple fact that the outcome being measured is the same.…”
Section: Discussionmentioning
confidence: 58%
“…The study received ethical approval from the York Research Ethics Committee. Inclusion criteria were 1) diagnosis of MS according to the 2010 revision of McDonald's criteria 8 2) ability to read and understand written English, 3) consent to participate in the trial, 4) able to attend two appointments 4 to 8 weeks apart. Patients with cognitive issues that would impair understanding of the questionnaires were excluded from the trial.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Mental Health Composite, MHC) [11]. A filter question ('During the past 4 weeks, have you had an active sexual life?')…”
Section: Pro Measuresmentioning
confidence: 99%
“…The technique provides several advantages in the assessment of health outcomes that are not directly measurable by offering a framework for item selection and the benefit of allowing comparisons across diseases and subgroups [28]. A number of outcome measures including the Short WEMWBS [8], Patient-Reported Outcomes Measurement Information System (PROMIS) [29], EUROHIS-QOL 8-item index, a short version of the 26item WHO Quality of Life questionnaire (WHOQOL-BREF) [30] and the Multiple Sclerosis Quality of Life (MSQOL)-54 [31] were developed using Rasch analyses. Such patient reported and preference based outcome measures usually have ordinal scales and are prone to high floor or ceiling effects [32]; Rasch analysis has been particularly useful in reducing these.…”
Section: Discussionmentioning
confidence: 99%